The urban transport companies in Spain: analysis of efficiency with data envelopment analysis. - Flores Ureba, Sandra; Simón de Blas, Clara; Sánchez-Toledano, Joaquín Ignacio; Sánchez de Lara, Miguel Ángel (Emerald, 2024)
Purpose This paper aims to define the efficiency achieved by urban transport companies in Spain concerning the resources they use, considering the type of management used for implementation, public-private, and size. Design/methodology/approach This study consisted of an analysis of the efficiency of 229 public-private urban transport operators during the period 2012–2021 using Data Envelopment Analysis, the Malmquist Index and inference estimators to determine productivity, efficiency change into Pure Technical Efficiency Change (PTECH), and scale efficiency change. Findings Based on the efficiency analysis, the authors concluded that of the 229 companies studied, more than 35 were inefficient in all analysed periods. Considering the sample used, direct management is considered significantly more efficient. It cannot be concluded that the size of these companies influences their efficiency, as the data show unequal development behaviours in the studied years. Originality/value This study provides arguments on whether there is a significant difference between the two types of management in the urban transport sector. It also includes firm size as a study variable, which has not been previously considered in other studies related to urban transport efficiency. Efficiency should be a crucial factor in determining funding allocation in this sector, as it encourages operators to optimize and improve their services.
Keywords: Transporte - España - Gestión; Efficiency; Urban transport; Data envelopment analysis